Influence of cesium cations on the formation of phosphates in aqueous solutions of the system Ca2+—Cs+—M+—PO43–—NO3 – (M+ — Na+, K+) - Livitska, O.V.; Strutynska, N. Yu.; Slobodyanik, M.S. (Reports of the National Academy of Sciences of Ukraine, 2018)
Peculiarities of the influence of cesium cations on the formation of calcium phosphates at the coprecipitation from aqueous solutions of the systems Ca2+—Cs+—M+—PO43–—NO3– (M+ — Na+, K+) (at the molar ratios Ca2+/PO43– = 1.67; M+/Cs+ = 1.0 and 2.0) have been investigated. The samples have been characterized using the powder X-ray diffraction method, FTIR-spectroscopy, scanning electron microscopy, and elemental ana lisys. It is found that cesium cations cause the formation of phases based on α-Ca3(PO4)2 at the precipitation from aqueous solutions.